Travel - Miller, Robert F. (Robert Finch) 1944- (Careers without college, 1993)
Describes five jobs in the world of travel (travel agent, flight attendant, reservations agent, customer service agent, tour manager), none of which requires a college degree, and discusses the skills needed to do them, their advantages and disadvantages, and their growth potential.